2022
DOI: 10.21203/rs.3.rs-1474372/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preterm Birth among Pregnant Persons with Severe Acute Respiratory Syndrome Coronavirus 2 Infection

Abstract: Background: Pregnant persons with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection are at increased risk of preterm birth, and evidence suggests this risk may be higher among pregnant persons with severe coronavirus disease 2019 (COVID-19) or among those infected later in pregnancy. However, the relationship between trimester of SARS-CoV-2 infection, severity of COVID-19, and preterm birth is not fully understood.Objective: This study examined the relationship between trimester of SARS-Co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…1 A previous analysis of SET-NET data indicated that, among people with SARS-CoV-2 infection during pregnancy, critical COVID-19 illness was associated with an increased risk of preterm birth compared to those with mild-to-severe COVID-19 illness. 25 Differences in characteristics between pregnant people with and without SARS-COV-2 infection may explain the higher preterm rates in this cohort. 26 COVID-19 in pregnancy is associated with adverse fetal and infant outcomes in addition to risk of severe disease for the pregnant person themselves, necessitating access to safe and effective vaccines, as well as treatment.…”
Section: Comments Principal Findingsmentioning
confidence: 91%
“…1 A previous analysis of SET-NET data indicated that, among people with SARS-CoV-2 infection during pregnancy, critical COVID-19 illness was associated with an increased risk of preterm birth compared to those with mild-to-severe COVID-19 illness. 25 Differences in characteristics between pregnant people with and without SARS-COV-2 infection may explain the higher preterm rates in this cohort. 26 COVID-19 in pregnancy is associated with adverse fetal and infant outcomes in addition to risk of severe disease for the pregnant person themselves, necessitating access to safe and effective vaccines, as well as treatment.…”
Section: Comments Principal Findingsmentioning
confidence: 91%